Investigation into multifunctional nanoparticles for the detection, imaging and intervention of amyloid - Xia, Yang (2019)
Amyloid is defined as insoluble, extracellular, proteinous aggregates formed by misfolding of proteins or peptides which are normally soluble. In the human body, amyloid is toxic and can cause cell death. Therefore, the presence of amyloid is linked with several diseases, including Alzheimer’s disease (AD), spongiform encephalopathies and type II diabetes, which are also referred as amyloidosis. AD is one of the most well-known amyloidoses. In AD, the amyloid aggregates appear predominantly in the patients’ brain, composed by a certain group of peptides known as amyloid beta (Aβ) peptides. Current clinical diagnoses of AD are primarily based on cognitive symptoms. However, it is often too late for intervention when the symptoms are detectable and there is no effective treatment for AD. On the other hand, the onset of amyloid aggregation may start years before the appearance of AD symptoms. Therefore, the detection and intervention of AD related amyloid at the molecular level are expected to be developed as powerful diagnostic and therapeutic methods for AD. Nanoparticle facilitated therapy and diagnosis have recently achieved impressive success in biomedical researches, especially in oncology studies. Compared to small molecule based probes and drugs, nanoparticles are capable to generate more comprehensive diagnosis, enhanced therapeutic effect, and better specific targeting. However, the reported applications of nanoparticles for AD research are still limited. In this context, by identifying the aforementioned research gap, this thesis aims to investigate the potential of nanoparticles for the early detection, imaging, and intervention of amyloid. To fulfill this objective, three nanoparticles: gold nanoparticles (AuNPs), carbon dots (C-dots) and iron oxide nanoparticles (IONPs), have been selected due to their unique physiochemical properties. Over the past decade, SERS spectroscopy has been utilized as a powerful analytical tool in chemistry, material science, and biomedical research. It is capable of revealing the conformational changes and structural differences between different molecules with high sensitivity. In addition, fluorescent imaging can be integrated with SERS spectroscopy as a comprehensive modality. In this thesis, a bi-functional SERS/fluorescent amyloid nanoprobe was prepared by conjugating Rose Bengal (RB) with AuNPs. Upon this conjugation, the characteristic Raman scattering of RB was significantly enhanced. Furthermore, when exposed to Aβ42 peptides, a detectable change was observed in the SERS spectrum of the RB-AuNPs conjugates. Also, the interaction between RB-AuNPs and Aβ42 induced fluorescence enhancement, which was utilized to perform ex vivo fluorescent imaging of amyloid plaques in transgenic mouse brains. C-dots are quantum sized (<10 nm) photoluminescent (PL) carbon particles. Bottom-up synthesized C-dots were prepared by hydrothermal pyrolysis of sucrose. Two types of passivation agents were added prior to the pyrolysis to generate PEG passivated C-dots (CD-G), and PEI passivated C-dots (CD-I). Both types of C-dots were then used to modulate the fibrillization process of Aβ42. Opposite effects were observed when mixing the two types of C-dots with Aβ42 peptides: CD-G could promote Aβ42 fibrillization while CD-I could inhibit it. Through a cell viability assay it was found that both types of C-dots could effectively reduce the cytotoxicity of Aβ42 peptides. These findings demonstrate that C-dots hold a great potential as low-cost, biocompatible nanoinhibitors for AD treatment. While most AD researches are focused on extracellular amyloids, intracellular amyloid is also playing a vital role in the pathogenesis of AD. The cellular uptake of extracellular amyloid by certain neuronal cells is a major source for intracellular amyloid build-up. To target these neuronal cells, dye labelled Aβ42 peptides were conjugated with IONPs. The produced magnetofluorescent IONPs shows enhanced and selective targeting of SH-SY5Y neuroblastoma cells. This research shows that Aβ42 functionalized IONPs can be used as bifunctional nanoprobes to interrogate the cellular uptake of amyloid. In general, this PhD thesis investigated the synthesis and utilization of multifunctional nanoparticles for the detection, imaging, and intervention of amyloid. It is envisaged that the results and research outcomes detailed in this thesis can lead to the realization of such nanoparticle-based amyloid probes for the diagnosis, and inhibitors for the treatment, of AD.